A tool to improve competence in the management of emergency patients by rural clinic health workers: a pilot assessment on the Thai-Myanmar border - Stanley, L; Min, T; Than, H; Stolbrink, M; McGregor, K; Chu, C; Nosten, F; McGready, R (BioMed Central, 2015)
BACKGROUND: Shoklo Malaria Research Unit has been providing health care in remote clinics on the Thai-Myanmar border to refugee and migrant populations since 1986 and 1995, respectively. Clinics are staffed by local health workers with a variety of training and experience. The need for a tool to improve the competence of local health workers in basic emergency assessment and management was recognised by medical faculty after observing the case mix seen at the clinic and reviewing the teaching programme that had been delivered in the past year (Jan-13 to March-14). AIMS: To pilot the development and evaluation of a simple teaching tool to improve competence in the assessment and management of acutely unwell patients by local health workers that can be delivered onsite with minimal resources. METHODS: A structured approach to common emergencies presenting to rural clinics and utilizing equipment available in the clinics was developed. A prospective repeated-measures observed structured clinical examination (OSCE) assessment design was used to score participants in their competence to assess and manage a scenario based 'emergency patient' at baseline, immediately post-course, and 8 weeks after the delivery of the teaching course. The assessment was conducted at 3 clinic sites and staff participation was voluntary. Participants filled out questionnaires on their confidence with different scenario based emergency patients. RESULTS: All staff who underwent the baseline assessment failed to carry out the essential steps in initial emergency assessment and management of an unconscious patient scenario. Following delivery of the teaching session, all groups showed improved competence in both objective assessment and subjective confidence levels. CONCLUSIONS: Structured and practical teaching and learning with minimal theory in this resource limited setting had a positive short-term effect on the competence of individual staff to carry out an initial assessment and manage an acutely unwell patient. Health-worker confidence likewise improved. Workplace assessments are needed to determine if this type of skills training impacts upon mortality or near miss mortality patients at the clinic.